Definition of the Descriptivism in the Modern Arabic Linguistic Study (Journal of Hama University, 2020)
The research seeks to highlight an aspect of the theoretical receiving of the Western Descriptivism in the modern Arabic linguistic studies by standing on one part. This part is the theoretical definition of the founders of the Arabic Descriptivism with their method that they brought from the West and applied to the Arabic language. This will be the objective to present Descriptivism definitions in some Western lexicons and then to identify their counterparts in Arabic linguistic lexicons in order to explain the difference between them in clarifying Descriptivism concepts. The research will also move to display the work of the founders of Arabic Descriptivism in their theoretical definitions through comparison, tracing, and evaluation because of the importance of these definitions in establishing scientific theories and in affecting the practical application.